Peran badan pengawas pemilu dalam pencegahan serta penanganan politik uang di Kota Madiun - Wahyu, Fairuz Syah Putra (Maliki Interdisciplinary Journal, 2023)
This research journal has the goal of analyzing the role of the Madiun City Bawaslu, to prevent the practice of money politics in the City of Madiun. Bawaslu, as the body that oversees the election process according to its main duties and functions, is obliged to provide a thorough oversight of every stage of the general election process so that elections are held that are fair, honest, transparent, and democratic. Bawaslu is also required to follow up on alleged violations related to the holding of elections, which arise from reports or investigation results. To carry out its duties, functions and performance, several violations that often occur accompany the stages in the implementation of general elections in Indonesia, namely money politics. Money politics will have implications for democratic values. The results of this study found that the efforts made by the Madiun City Bawaslu in preventing money politics are by providing socialization to the community as well as giving warnings to those who carry out money politics or money politics.